Green Synthesis of Copper Nanoparticles Using Syzygium polyanthum Extract and Their Antioxidant Potential via DPPH Assay - Nasution, Shamila Sufi Aulia; Miswanda, Dikki; Ridwanto, Ridwanto; Dalimunthe, Gabena Indrayani (Pustaka Media Publishing, 2025)
Copper nanoparticles (CuNPs) have gained attention for their cost-effective synthesis and potent antioxidant properties, offering a promising approach to address the bioavailability challenges of herbal medicines. This study investigates the green synthesis of CuNPs using bay leaf (Syzygium polyanthum (Wight.) Walp.) extract as a bioreductor and evaluates their antioxidant activity via the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. Bay leaf extract, rich in flavonoids and phenolic compounds, was prepared through heating extraction and mixed with copper nitrate (CuNO₃) at varying ratios (1:1, 1:2, 1:3, 1:4). The formation of CuNPs was confirmed by a color change from yellow to greenish-brown after 24 hours, with particle sizes ranging from 527.48 nm to 3256.81 nm, as determined by Particle Size Analysis (PSA). UV-Vis spectrophotometry verified the reduction of Cu⁺ ions, with Cu concentrations decreasing post-synthesis. The antioxidant activity of CuNPs exhibited an IC₅₀ value of 15.49 ppm, classified as very strong, compared to 72.09 ppm for the bay leaf extract alone (strong) and 13.82 ppm for vitamin C (very strong). These results demonstrate that bay leaf extract-mediated CuNPs possess enhanced antioxidant potential, highlighting the efficacy of green synthesis in producing bioactive nanoparticles for potential therapeutic applications.